A Taxon-Wise Insight Into Rock Weathering and Nitrogen Fixation Functional Profiles of Proglacial Systems - Varliero, Gilda; Anesio, Alexandre M.; Barker, Gary L. A. (Frontiers in Microbiology, 2021)
The Arctic environment is particularly affected by the global warming and a clear trend of the ice retreat is observed worldwide. In proglacial systems, the newly exposed terrain represents different environmental and nutrient conditions compared to later soil stages. Therefore, proglacial systems show several environmental gradients along the soil succession where microorganisms are active protagonist of the soil and carbon pool formation through nitrogen fixation and rock weathering. We studied the microbial succession of three Arctic proglacial systems located in Svalbard (Midtre Lovénbreen), Sweden (Storglaciären) and Greenland (foreland close to Kangerlussuaq). We analyzed sixty-five whole shotgun metagenomic soil samples for a total of more than 400 Gb of sequencing data. Microbial succession showed common trends typical of proglacial systems with increasing diversity observed along the forefield chronosequence. Microbial trends were explained by the distance from the ice edge in the Midtre Lovénbreen and Storglaciären forefields, and by TN and TOC in the Greenland proglacial system. Further, we focused specifically on genes associated to nitrogen fixation and biotic rock weathering processes, such as nitrogenase genes, obcA genes and genes involved in cyanide and siderophore synthesis and transport. Whereas we confirmed the presence of these genes in known nitrogen fixing and/or rock weathering organisms (e.g. Nostoc, Burkholderia), in this study we also detected organisms that, even if often found in soil and proglacial systems, have never been related to nitrogen fixing or rock weathering processes before (e.g. Fimbriiglobus, Streptomyces). The different genera showed different gene trends within and among the studied systems, indicating a community constituted by a plurality of organisms involved in nitrogen fixation and biotic rock weathering, and where the latter were driven by different organisms at different soil succession stages.